The Utility of Serum Receptor-Binding Cancer Antigen Expressed on Siso Cells in Gastrointestinal Tract Cancers - Şahin Çoban; Hasan Özkan; Seyfettin Köklü; Osman Yüksel; Muhammed Cem Koçkar; Tarik Akar; Necati Örmeci (Canadian Journal of Gastroenterology)
BACKGROUND: Receptor-binding cancer antigen expressed on SiSo cells (RCAS1) is a novel tumour marker that has been described in various kinds of cancer. The majority of observations include immunohistochemical studies; however, there are not enough data about the utility of this antigen as a serum tumour marker and its tumour specificity.